Exploring classroom practices associated with greater student engagement that may benefit low-income students in the early grades - Christopher, Caroline; Newman, Katherine (Frontiers in Education, 2022)
Previous research has identified specific classroom practices that are associated with greater academic and self-regulation gains for students in prekindergarten (PreK) and kindergarten (K) classrooms (Farran et al., 2017; Christopher & Farran, 2020). These practices include reducing time in transition, more time in sequential activities, more opportunities for associative and cooperative interactions, more math, teachers’ using higher levels of instruction, positive classroom climate, and more teacher listening to children. This cross-sectional study aims to determine whether these specific classroom practices are associated with higher student engagement. A secondary goal was to examine whether economically disadvantaged (ED) students in more engaged classrooms scored higher on measures of math, language, and literacy. Researchers collected individual student assessment data in math, language, and literacy for a sample of 407 PreK and K students and conducted day-long observations in their classrooms. In addition to collecting behavioral count data on the focal classroom practices, observers rated students’ engagement across the day. Results revealed that students who experienced more of the beneficial classroom practices also showed higher engagement. Covariate-adjusted standardized mean difference effect sizes showed the greatest differences for transition time, sequential activities, associative and cooperative interactions, teachers’ listening, the amount of instruction, behavior approvals, and teacher tone, indicating that students experiencing more of these practices were more engaged than students experiencing fewer of these practices. To address our secondary goal of exploring between-group differences on assessments, we created groups based on ED status and engagement (operationalized using a median split for student engagement). While assessment scores were higher for non-ED students than ED students, regardless of their level of engagement, based on the literature researchers expected that ED students who were more engaged would have higher scores on assessments than their less engaged counterparts. Contrary to this hypothesis, there were few differences across groups. The largest positive effect sizes were for math and vocabulary. ED students with higher engagement had lower, not higher, scores on measures of literacy and passage comprehension. However, the magnitude of these effect sizes was small. Results provide preliminary evidence that these specific classroom practices are associated with greater student engagement.